Evaluation of the quality, reliability, and views of videos available on YouTube® on the therapeutic use of amber necklaces for babies in the tooth eruption phase (Research, Society and Development, 2025)
Objective: the aim of this study was to analyze and evaluate the quality, reliability and views of the videos available on YouTube® as a source of information, related to the therapeutic use of the amber necklace for babies during the period of tooth eruption. Method: A search was performed on YouTube®, on March 20, 2024. The term chosen for the search was " baby amber necklace" on the Google Trends website. As an inclusion criterion, the videos should contain information about the use of amber necklace as a therapy to reduce the symptoms of tooth eruption in babies. The videos were analyzed for the reliability of the information, based on a 5-point scale, adapted from the DISCERN tool, and for quality with the Global Quality Score (GQS) tool, which ranges from 1-poor quality to 5-excellent quality. Results: A total of 22 videos were found with the search term, 15 of which were selected. The quality frequency GQS “1” was the highest and it was observed that there was a difference in quality between the origins of the videos (p